Intra‐individual biological variation in sweat chloride concentrations in CF, CFTR dysfunction, and healthy pediatric subjects. Issue 6 (2nd April 2018) - Cirilli, Natalia; Raia, Valeria; Rocco, Ilaria; De Gregorio, Fabiola; Tosco, Antonella; Salvadori, Laura; Sepe, Angela Ornella; Buzzetti, Roberto; Minicuci, Nadia; Castaldo, Giuseppe
Abstract: Background: The sweat test is one of the main diagnostic tools used in newborn screening programs and as a confirmatory test, in case of suspect of Cystic Fibrosis (CF). Since sweat chloride (Cl) concentration is also considered an appropriate parameter to explore the efficacy of CFTR modulators in clinical trials, it is crucial to evaluate the biological variability of this test in healthy and pathological conditions. The aim of this pilot study was to determine the intra‐individual biological variability of sweat Cl, both in healthy individuals and CF patients and to assess its correlation with diet, season, and menstrual cycle. Methods: Thirty‐five out of 36 selected subjects (6‐18 years) were enrolled by 2 CF care centers and assigned to 3 cohorts: CF, CFTR‐related disorder (CFTR‐RD) and healthy volunteers. Each participant was subjected to eight sweat tests in different conditions and time of the year. Data were analyzed using linear mixed effects models for repeated measures, taking also into account intra‐individual correlations. Results: We observed a high intra‐individual variability of sweat Cl, with the lowest mean CV% values among CF patients (20.21 in CF, 29.74 in CFTR‐RD, and 31.15 in healthy subjects). Gender and diet had no influence on sweat Cl variability, nor had pubertal age and menstrual phase. Conclusion: Results of this pilot study confirmed that sweat Cl variability is high in CF patients, although non‐CF individuals displayed even higher mean CV% values. Season significantly influenced sweat test values only in CF patients, likely due to changes in their hydration status.